2018 IFPRI annual report - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
IFPRI’s 2018 Annual Report shares highlights of our work, which together with partners has helped to develop and tailor knowledge to local contexts, build human and institutional capacity, and support development strategies in many countries around the world. Research findings and policy developments related to fostering climate resilience, agricultural transformation, healthy diets, inclusive and efficient markets, institutions and governance, and gender are presented, along with updates on other IFPRI areas of work.